The relationship of safety management practice toward safety behavior among UUM student athletes - Mohd Aizul Firdaus, Musa (2018)
The safety management practice has positive impact with safety behavior. In recent years, the accidents and injury caused by participating in the sports activities were increasing rapidly. Moreover, the rising numbers of accident rate in the environment of sports and recreation can bring the negative influence on the sports industry. Therefore, this study was intended to identify the relationship of safety management practice with safety behavior among the student athletes in Universiti Utara Malaysia (UUM). The respondent in this study were athletes who had been actively using the facilities in the UUM Sports Centre. Self-administrative questionnaires had been used in this study which involve 120 respondents. As the result, the correlation and regression revealed that safety management practice were positively and significantly related with safety behaviour. Hence, a lots of efforts, commitments, resources, enforcements and enhancements need to be done by the management in order to improve the quality of safety management practice and make the safety behavior as a culture in the UUM Sports Centre.